Highlights in Focus Issue on Prostate Cancer - Xu, Eunice X. (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
In September 2013, the Translational Andrology and Urology (TAU) launched a focus issue on “Prostate Cancer”, which was guest-edited by Dr. Jer-Tsong Hsieh and Dr. Ganesh Raj from University of Texas Southwestern Medical Center at Dallas, USA.